Impaired Glucose Tolerance in Patients with Polycystic Ovarian Syndrome - Bushra Anwar, Faiza, Sarwar Malik, Muhammad Qasim, Malik Fayaz, Shah Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovary syndrome first described by Stein and Leventhal, is a complex genetic trait of unclear etiology characterized by Oligomenorrhea or anovulation, biochemical or clinical hyperandrogenism and polycystic ovarian morphology on ultrasonography. Women with polycystic ovarian syndrome have an increased risk of developing impaired glucose tolerance and type 2 diabetes mellitus. This study aims to determine the prevalence of impaired glucose tolerance in patients with polycystic ovary syndrome. Study Design: Cross-sectional study Study Duration: This study was conducted in the Department of Endocrinology Ayub Teaching Hospital Abbottabad from 1st Nov 2021 to 30th April 2022. Materials and Methods: All patients with age range 16 to 40 years who were diagnosed with polycystic ovarian syndrome were included in the study. Age, ovarian volume, clinical signs of hyperandrogenism, menstrual abnormalities, serum testosterone, blood glucose at baseline and following 75g of oral glucose load, Body mass index etc. were recorded. Data was analyzed using SPSS-23. Results: Among 139 patients, 35(25.2%) were in the age range 16-25 years while 104(74.8%) were in the age range 26-40 years. Mean age was 28.6(SD±4.2) years. 69(49.6%) patients had BMI> 30 Kg/m2, 60(43.2%) had BMI between 25-29.9 Kg/m2, while only 10(7.2%) patients had their BMI within normal range (18.5-24.9). Mean BMI was 30.7 Kg/m2 (SD±4.4). 47(33.8%) patients had ovarian volume less than 25ml while, 92(66.2%) had ovarian volume greater than 25ml. Mean ovarian volume was 25.5(SD±6.7). 106(76.3%) patients had serum testosterone less than 70ng/dl while, 33(23.7%) had serum testosterone greater than 70ng/dl. Mean serum testosterone was 48.8(SD±26.4). Hirsutism and Acne was observed in 92 (66.2%) and 91(65.5%) patients respectively. 75 (54%) women had positive family history of Diabetes, 56 (40.3%) had family history of polycystic ovary syndrome and 71 (51.1%) patients had past or current history of oral contraceptive pills. Impaired glucose tolerance was found in 52(37.4%) patients. Post stratification results were statistically significant. Conclusions: The prevalence of impaired Glucose tolerance with polycystic ovary syndrome can be as high as 37.4%. Increasing age and Body Mass Index, raise serum testosterone level and increasing ovarian volume are significant predictors for developing impaired glucose tolerance in women with polycystic ovary syndrome. Keywords: Polycystic Ovarian Syndrome, Impaired Glucose Tolerance, Predictive Factors.